Services, technologies, and systems at Ka band and beyond-a survey. - Gargione, F. (IEEE Journal on selected areas in communications)
This paper discusses system and technology aspects crucial to the development of satellite communications at Ka band (20-30 GHz) and beyond. It surveys the evolution of Ka band geostationary Earth orbit (GEO) satellite communications until the present stage of development of systems for direct-to-user (DTU) provision of interactive multimedia services worldwide. Then it discusses the attenuation problem and main technical issues of this new technology. Finally, it provides a view on experiments and technological developments at extremely high-frequency (EHF) bands